Coordinative Practices in the Building Process An Ethnographic Perspective - Christensen, Lars Rune.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Coordinative Practices in the Building Process: An Ethnographic Perspective presents the principles of the practice-oriented research programmes in the CSCW and HCI domains, explaining and examining the ideas and motivations behind basing technology design on ethnography. The focus throughout is on generating ethnographically informed accounts of the building process and discussing the concepts of cooperative work and coordinative practices in order to frame technology development. Lars Rune Christensen provides an invaluable resource for these communities in this book. Illustrated with real examples from the building process, he reports on the cooperative work and coordinative practices found, allowing readers to feel that they know, from the point of view of the people working in the building process, what it is like to coordinate and do this kind of cooperative work.
Preface -- Introduction -- The Practice-oriented Research Program in CSCW -- The View from Organizational Studies -- Introduction to the Building Process -- The Relationship between Design and Construction -- Apprenticeship and Visual Skills -- Coordinative Practices -- On the Concept of Intrinsic Coordination -- Implications for CSCW -- Subject Index.
Keywords: Computer science; Anthropology; Computer Science; User Interfaces and Human Computer Interaction; Anthropology